2015
DOI: 10.14214/df.194
|View full text |Cite
|
Sign up to set email alerts
|

Soil CO2 efflux in boreal pine forests in the current climate and under CO2 enrichment and air warming

Abstract: The aims of the study were to identify factors related to temporal and spatial variation in forest soil CO2 efflux (Fs), compare measurement chambers, and to test effects of a climate change experiment. The study was based on four-year measurements in upland Scots pine forests. Momentary plot averages of Fs ranged from 0.04 to 1.12 gCO2m −2 h −1 and annual estimates for the forested area from1750 to 2050 gCO2m −2. Soil temperature was a dominant predictor of the temporal variation in Fs (R 2 =76-82%). A temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2015
2015
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 242 publications
(445 reference statements)
2
4
1
Order By: Relevance
“…The significant decrease in labile SOC at the 10–20 cm depth with warming was in contrast to a previous study that warming increased soil microbial biomass C and labile organic C in a tallgrass prairie [16]. However, our finding was supported by previous studies in which warming decreased microbial biomass C [22] and soil respiration [3], [4]. The discrepancy between results from our grassland study and the tallgrass prairie study [16] could be due to complexity of ecosystems and various key controlling factors for C cycling in different ecosystems [23].…”
Section: Resultscontrasting
confidence: 58%
“…The significant decrease in labile SOC at the 10–20 cm depth with warming was in contrast to a previous study that warming increased soil microbial biomass C and labile organic C in a tallgrass prairie [16]. However, our finding was supported by previous studies in which warming decreased microbial biomass C [22] and soil respiration [3], [4]. The discrepancy between results from our grassland study and the tallgrass prairie study [16] could be due to complexity of ecosystems and various key controlling factors for C cycling in different ecosystems [23].…”
Section: Resultscontrasting
confidence: 58%
“…Warming significantly increased soil CO 2 efflux at both study sites, albeit the effects of this treatment were affected by both RE and biocrust cover in Aranjuez. Our findings agree with results from experiments conducted in a wide variety of environments, which have reported significant increases in soil CO 2 efflux with warming during the first years (typically between 20% and 40%), which are later reduced due to acclimatization processes (Rustad et al ., ; Luo et al ., ; Niinistö et al ., ; but see Lellei‐Kovács et al ., ; de Dato et al ., ). Differences between sites in the magnitude of warming effects with biocrust development may have caused by variations in overall fertility, as soil CO 2 efflux has been found to be influenced not only by moisture and temperature, but also by the amount of available soil organic carbon (Sponseller, ; Moyano et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The effects of diurnal warming on soil respiration or ecosystem carbon exchange were not equal to the separate effects of day and night warming in a temperate steppe (Xia et al, 2009). However, studies of soil CO 2 emission to multiple environmental conditions found that response to temperature was by far the most dominant one (Edwards & Norby, 1998;Lin et al, 2001;Niinist€ o et al, 2004;Zhou et al, 2006). Soil CO 2 emission increased with temperature, largely independent of the changes of other factors.…”
Section: Introductionmentioning
confidence: 99%